A tunable photonic RF phase shifter using single semiconductor optical amplifier. Issue 2 (February 2014) - Chen, Han; Sun, Mingming; Ding, Yi; Sun, Xiaohan
ABSTRACT A continuously tunable linear radio frequency phase shifter based on polarization interference in single semiconductor optical amplifier is presented, and the theoretical fundamentals of the design are explained. A prototype of the phase shifter with 10‐GHz bandwidth and far beyond 360° tuning range is experimentally demonstrated. © 2014 Wiley Periodicals, Inc. Microwave Opt Technol Lett 56:340–343, 2014